The Conversion of Communal Land Ownership for Economic Activity: A Study on the Resilience of Customary Law Community in Response to State Policy - Irawan, Bimbi; Soetarto, Endriatmo; Ekayani, Meti; Zain, Alinda F.M. (Universitas Andalas, 2023)
Communal land, the dominant form of land ownership in West Sumatra Province, is a legal place customarily to carry out economic activities with the principle of mutual benefit, and no transfer of communal land ownership is permitted. However, current state policies in economic activity tend to change the form of communal land ownership. The legality constructed by the state has made the transfer of ownership of communal land when used for economic activity, which disrupts the system of ownership and tenure of communal land. These conditions led to the emergence of community resilience in maintaining ownership and tenure of communal land. The method used in this research is a case study in two villages/ nagari, where data collection was carried out through in-depth interviews with several elements in the nagari. Community resilience is carried out by converting communal land ownership from nagari communal land to clan or subclan communal land and vice versa. The conversion of ownership type is a form of the resilience of the community against state policies that threaten communal land ownership and tenure while at the same time maintaining a balance of social and economic benefits from the use of communal land for economic activity.